2017
DOI: 10.1242/dev.137216
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms of tooth root development

Abstract: The tooth root is an integral, functionally important part of our dentition. The formation of a functional root depends on epithelialmesenchymal interactions and integration of the root with the jaw bone, blood supply and nerve innervations. The root development process therefore offers an attractive model for investigating organogenesis. Understanding how roots develop and how they can be bioengineered is also of great interest in the field of regenerative medicine. Here, we discuss recent advances in underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
221
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(243 citation statements)
references
References 101 publications
(107 reference statements)
3
221
0
2
Order By: Relevance
“…The unpredictability of root maturation of immature permanent teeth with a necrotic pulp after RET is likely due to the disturbance in interaction between Hertwig's epithelial root sheath and mesenchymal stem cells in the dental follicle (Li et al . ). The severity of the inflammatory apical lesion may damage or affect the biological function of Hertwig's epithelial root sheath and mesenchymal stem cells in the periapical area.…”
Section: Is Root Maturation Predictable After Ret?mentioning
confidence: 97%
“…The unpredictability of root maturation of immature permanent teeth with a necrotic pulp after RET is likely due to the disturbance in interaction between Hertwig's epithelial root sheath and mesenchymal stem cells in the dental follicle (Li et al . ). The severity of the inflammatory apical lesion may damage or affect the biological function of Hertwig's epithelial root sheath and mesenchymal stem cells in the periapical area.…”
Section: Is Root Maturation Predictable After Ret?mentioning
confidence: 97%
“…To mimic this biological process for tooth root regeneration, future studies will need to investigate the coordination between these components. In addition, previous studies have shown that epithelialmesenchymal interactions are crucial for tooth development as well as many other developmental processes (Li et al, 2017). At early embryonic stages, BMP signaling is relayed between the epithelium and mesenchyme as tooth development progresses.…”
Section: Bmp-regulated Mscs May Be Useful For Tooth Regeneration Apprmentioning
confidence: 99%
“…The way to regulate the amount of oxygen and nutrients of a specific area in a tissue is through angiogenesis (Roberts-Clark & Smith 2000, Li et al 2017, Xue et al 2018. The way to regulate the amount of oxygen and nutrients of a specific area in a tissue is through angiogenesis (Roberts-Clark & Smith 2000, Li et al 2017, Xue et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Then, HERS becomes perforated due to apoptosis after its movement towards the apical region of the tooth forming a network structure that will serve as a pattern for dental root formation and will facilitate the interaction between dentine, cementum and periodontal ligament (Luan et al 2006, Huang et al 2009, Li et al 2017. Then, HERS becomes perforated due to apoptosis after its movement towards the apical region of the tooth forming a network structure that will serve as a pattern for dental root formation and will facilitate the interaction between dentine, cementum and periodontal ligament (Luan et al 2006, Huang et al 2009, Li et al 2017.…”
Section: Introductionmentioning
confidence: 99%